French Prison Day Leave and the Rationale Behind It: Resocialisation or Prison Management? - Herzog-Evans, Martine (European journal on criminal policy and research, 2020)
In France, prison leave (permission) is awarded to prisoners by a reentry judge (juge de l’application des peines, JAP) as part of a multi-agency commission, a process that takes place in prison and comprises the governor, prison and probation officers, and the prosecutor. Numerous rules govern this measure. This paper draws upon a number of previous research studies conducted by the author on the following topics: the legal theorisation of a sentence’s implementation (Author 1994 , 2017a); a quantitative-qualitative study of JAPs’ practices, hearings and rulings (Author 2014); and a mixed method study of a so-called swift release procedure (Author 2017b). Consequently, two series of issues are identified: The first issue pertains to the lack of due process principles governing the decision-making process. Prisoners who apply for permissions have no ‘voice’, according to Tyler’s (2012) definition of the term. The second issue is connected to the very rationale behind permissions. Before an Act of 26 March 2019, permissions were primarily concerned with ensuring that prisoners’ reentry process was prepared, that prisoners could complete the steps required to prepare for their release and that they could maintain contact with their loved ones and support systems. They also represented a form of test, used by JAPs to ensure that prisoners could be trusted in the outside world. In other words, they were focused on resettlement and rehabilitation. However, the 2019 Act transferred most of the decision-making process to prison governors. There is now a fear that because their main interest is on maintaining order, permission allocation will shift from an emphasis on reentry-rehabilitation to behavioural criteria and the local situation regarding overcrowding.